Design and development of a mixed reality teaching systems for IV cannulation and clinical instruction - Xiong, Wei; Peng, Yingda (Computer animation and virtual worlds, 2024)
Intravenous cannulation (IV) is a common technique used in clinical infusion. This study developed a mixed reality IV cannulation teaching system based on the Hololens2 platform. The paper integrates cognitive‐affective theory of learning with media (CATLM) and investigates the cognitive engagement and willingness to use the system from the learners' perspective. Through experimental research on 125 subjects, the variables affecting learners' cognitive engagement and intention to use were determined. On the basis of CATLM, three new mixed reality attributes, immersion, system verisimilitude, and response time, were introduced, and their relationships with cognitive participation and willingness to use were determined. The results show that high immersion of mixed reality technology promotes students' higher cognitive engagement; however, this high immersion does not significantly affect learners' intention to use mixed reality technology for learning. Overall, cognitive and emotional theories are effective in mixed reality environments, and the model has good adaptability. This study provides a reference for the application of mixed reality technology in medical education.